Revolução e republicanismo em Hannah Arendt - Fernandes, Antonio Batista (2023)
This thesis has as its main purpose to discuss the relationship between revolution and republicanism in Hanna Arendt’s works, aiming to sustain the strong influence of the modern and classic republican theory in the political thought of the aforementioned author. Therefore, we intend to analyze the works that discuss and sustain that perspective, such as On Revolution, The Human Condition, Between Past and Future, and Crises of the Republic, without disregarding other texts and works that are relevant to this study. The hypothesis that guides this research poses that Arendt, although cannot be considered a republicanism theorist, develop in her political theory a grammar that dialogues and approximates several concepts and categories of the republican grammar, significantly contributing to the resumption of the republican theory nowadays. At first, we supported the idea that the discussion about republicanism in Arendt’s work gains strength from her analysis of the modern revolutions, marked by the reflection on the concepts of freedom, public happiness, and the foundation of the Republic, as well as by her position in relation to the social issues and the defense of the dignity of politics. Then, we proceed to the analysis of Arendt’s critics on the sovereign Nation-State model, to which Arendt opposes the new north American federalist republican model. We believe that Arendt’s objective when discussing the foundation of the Republic issue is, above all, to ensure the spaces of democratic and political participation by republican institutions that are open to novelty and able to find political solutions for the limits and fragilities of the Republic itself. Therefore, we sustain that Arendt’s political theory decisively contributes to the development of the contemporary matrix of republicanism and, thus, can be placed in the tradition of republican thought